A class of limit theorems for conditional distributions - Kolchin, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Ф. Колчин. Один класс предельных теорем для условных распределенийV. Kolčinas. Viena ribinių teoremų klasė sąlyginiams pasiskirstymams